ZnO hollow spheres with double-yolk egg structure for high-performance photocatalysts and photodetectors - Wang, Xi (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.